Prognostic Role of Androgen Receptor Expression in Surgically Resected Early Breast Cancer Patients - Yang, Yaewon; Min, Ahrum; Lee, Kyung-Hun; Ryu, Han Suk; Kim, Tae-Yong; Woo, Go-un; Suh, Koung Jin; Lee, Dae-Won; Lee, Han-Byoel; Moon, Hyeong-Gon; Han, Wonshik; Park, In Ae; et al. (Journal of breast cancer, 2020)
Endocrine therapy is a standard treatment for hormone receptor-positive breast cancer, which accounts for 60%-75% of all breast cancer. Hormone receptor positivity is a prognostic and predictive biomarker in breast cancer. Approximately 50%-80% of breast cancer is also positive for androgen receptor (AR), but the prognostic and predictive value of AR expression in breast cancer is controversial. Here, we investigated AR expression and its prognostic value in patients with surgically resected breast cancer in Korea. We retrospectively reviewed the medical records of patients who had surgically resected breast cancer to collect AR expression data and other clinicopathological data. The optimal cut-off for AR positivity was determined using a receiver operating characteristic curve analysis. We reviewed 957 patients with surgically resected breast cancer from June 2012 to April 2013. The median follow-up was 62 months, and relapse events occurred in 101 (10.6%) patients. Unlike the cut-off value of 1% or 10% in previous reports, 35% was determined to be best for predicting relapse-free survival (RFS) in this study. At the cut-off value of 35%, 654 (68.4%) patients were AR-positive. AR expression was more prevalent in luminal A (87.6%) and luminal B (73.1%) types than in human epidermal growth factor receptor 2-positive (56.2%) or triple-negative (20.6%) types. AR expression of ≥ 35% was significantly related to longer RFS in a multivariate analysis (hazard ratio, 0.430; 95% confidence interval, 0.260-0.709; = 0.001). We propose a cut-off value of 35% to best predict RFS in patients with surgically resected breast cancer. AR expression was positive in 68.4% of patients, and AR positivity was found to be an independent prognostic factor for longer RFS.